Outcomes of fertility preservation treatments in patients with endometrial cancer with different molecular classifications based on an NGS panel - Yan Xu; Mingming Zhao; Li Zhang; Tianyou Wang; Bo Wang; Yu Xue; Zhiying Xu; Wenyu Shao; Xiaojun Chen; Chao Wang (Frontiers in Oncology, 2023)
BackgroundThe molecular classification of endometrial cancer has previously been shown to be associated with clinical outcomes. However, there are insufficient data to support the routine use of molecular classification for the treatment of patients seeking fertility preservation.MethodsHere, we retrospectively investigated 90 patients received fertility-sparing treatment. We used a next generation sequencing (NGS) panel to classify these patients into four subtypes. All patients received hormonal therapy combined with hysteroscopy. Therapeutic effects were evaluated by hysteroscopy every three months during the treatment.ResultsPatients with POLE mutations had the highest disease progression rate (50.0%, P=0.013), while the microsatellite instability-high (MSI-H) group had the highest recurrence rate (50.0%, P=0.042). PIK3CA mutation (hazard ratio (HR): 0.61; 95% confidence interval (CI): 0.37–0.99; P=0.046), overweight (HR: 0.56; 95% CI: 0.32–0.96; P=0.033) and obesity (HR: 0.44; 95% CI: 0.20–0.95; P=0.036) were associated with a significantly lower cumulative complete response (CR) rate. The combination of gonadotropin-releasing hormone analogues (GnRH-a) and letrozole (HR: 3.43; 95% CI: 1.81–6.52; P< 0.001) was associated with a significantly higher cumulative CR rate. KRAS mutation was significantly associated with disease progression (P=0.002). In wild-type TP53 patients, PTEN and PIK3CA mutations significantly prolonged the duration of treatment to achieve CR (log rank P=0.034; P=0.018).ConclusionThe implementation of molecular classification for EC patients undergoing fertility-sparing treatment is promising and can facilitate the selection of appropriate medical regimes to achieve better outcomes in patients with EC who require fertility preservation treatment.